Prediction of locally advanced urothelial carcinoma of the bladder using clinical parameters before radical cystectomy: a prospective multicenter study - Martini, Thomas; Moersdorf, Johannes Matthias; Hohenfellner, Markus (Urologia internationalis, 2016)
Introduction: We aimed at developing and validating a pre-cystectomy nomogram for the prediction of locally advanced urothelial carcinoma of the bladder (UCB) using clinicopathological parameters. Materials and Methods: Multicenter data from 337 patients who underwent radical cystectomy (RC) for UCB were prospectively collected and eligible for final analysis. Univariate and multivariate logistic regression models were applied to identify significant predictors of locally advanced tumor stage (pT3/4 and/or pN+) at RC. Internal validation was performed by bootstrapping. The decision curve analysis (DCA) was done to evaluate the clinical value. Results: The distribution of tumor stages pT3/4, pN+ and pT3/4 and/or pN+ at RC was 44.2, 27.6 and 50.4%, respectively. Age (odds ratio (OR) 0.980; p < 0.001), advanced clinical tumor stage (cT3 vs. cTa, cTis, cT1; OR 3.367; p < 0.001), presence of hydronephrosis (OR 1.844; p = 0.043) and advanced tumor stage T3 and/or N+ at CT imaging (OR 4.378; p < 0.001) were independent predictors for pT3/4 and/or pN+ tumor stage. The predictive accuracy of our nomogram for pT3/4 and/or pN+ at RC was 77.5%. DCA for predicting pT3/4 and/or pN+ at RC showed a clinical net benefit across all probability thresholds. Conclusion: We developed a nomogram for the prediction of locally advanced tumor stage pT3/4 and/or pN+ before RC using established clinicopathological parameters.
Gesehen am 13.02.2019
Published online: July 1, 2015